Molecular detection of Leishmania infantum in donkeys and mules under semiarid conditions in Brazil - Limeira, Clécio Henrique; de Oliveira, Murilo Duarte; Júnior, João Pessoa Araújo [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Silva, Maria Luana Cristiny Rodrigues; de Azevedo, Sérgio Santos; Alves, Clebert José (FapUNIFESP (SciELO), 2021)
Visceral leishmaniasis is a parasitic zoonosis that mainly affects poorest and most vulnerable populations, and domestic dogs are considered to be the main source of infection to the vector and therefore humans. However, several studies have investigated the role of other vertebrate hosts in the disease cycle. In this context, the aim of the present study was to conduct a survey of Leishmania infantum infection in donkeys and mules living in a semiarid region of Brazil. Whole blood sampled from 72 equids (65 donkeys and 7 mules) was used to perform molecular diagnosis using the real-time polymerase chain reaction (qPCR) technique. A total of 25% of the samples (18/72) were positive through qPCR, but there were no significant differences between the species (donkeys or mules), sex (male or female) and abandonment situation of the animals (yes or no). Donkeys and mules living under semiarid conditions have high frequency of L. infantum infection. It is therefore worth assigning importance to these species in the epidemiological cycle of visceral leishmaniasis, either as potential reservoirs or just as an abundant food source for vectors.
Detecção molecular de Leishmania infantum em asininos e muares sob condições semiáridas
Keywords: Epidemiology; Equids; Leishmaniosis; QPCR; Zoonosis